Osmotin: a plant sentinel and a possible agonist of mammalian adiponectin - Anil Kumar, S.; Hima Kumari, P.; Shravan Kumar, G.; Mohanalatha, C.; Kavi Kishor, P. B. (Frontiers in Plant Science, 2015)
Osmotin is a stress responsive antifungal protein belonging to the pathogenesis-related (PR)-5 family that confers tolerance to both biotic and abiotic stresses in plants. Protective efforts of osmotin in plants range from high temperature to cold and salt to drought. It lyses the plasma membrane of the pathogens. It is widely distributed in fruits and vegetables. It is a differentially expressed and developmentally regulated protein that protects the cells from osmotic stress and invading pathogens as well, by structural or metabolic alterations. During stress conditions, osmotin helps in the accumulation of the osmolyte proline, which quenches reactive oxygen species and free radicals. Osmotin expression results in the accumulation of storage reserves and increases the shelf-life of fruits. It binds to a seven-transmembrane-domain receptor-like protein and induces programmed cell death in Saccharomyces cerevisiae through RAS2/cAMP signaling pathway. Adiponectin, produced in adipose tissues of mammals, is an insulin-sensitizing hormone. Strangely, osmotin acts like the mammalian hormone adiponectin in various in vitro and in vivo models. Adiponectin and osmotin, the two receptor binding proteins do not share sequence similarity at the amino acid level, but interestingly they have a similar structural and functional properties. In experimental mice, adiponectin inhibits endothelial cell proliferation and migration, primary tumor growth, and reduces atherosclerosis. This retrospective work examines the vital role of osmotin in plant defense and as a potential targeted therapeutic drug for humans.